XIX դարի երկրորդ կեսին Կարինի նահանգում ժողովրդագրական փոփոխությունների պատճառները - Հովհաննես Զատիկյան (ՀՀ ԳԱԱ հրատ.)
Социально-экономические и политические отношения не имели другой цели, кроме влияния на демографические показатели, чтобы было обеспечено количественное преимущество народа-завоевателя. Путем анализа мы пришли к тому выводу, что в данных условиях становилась необходимой борьба за выживание западных армян, осуществляемое противодействие уничтожающей политике. The Socio-economic and political relationships had to exert an impact on the demographic data, in order to ensure quantitative advantages for the people who had conquered. Through investigations, we concluded that in similar circumstances, it has become a necessity for the Western Armenians to fight for survival, an achievable counteraction to the destructive policy.
Keywords: Modern History; Demography; Population; Vital Events